Global Ergonomics: A New Systems Paradigm for Preventing Work-Related Musculoskeletal Disorders in the Era of Global Health - Philippe Gorce (Theoretical and Applied Ergonomics, 2026)
Work-related musculoskeletal disorders (WMSDs) remain the leading cause of occupational disability worldwide, despite several decades of progress in ergonomics and occupational health [...]